A Case Report: Carcinoma of the Gastric Stump after Billroth II Resection - Chang, Sae Kyung (Korean J Intern Med, 1988)
Carcinoma of the gastric stump as a late complication for resection of benign disease is a well recognized clinical entity. The risk of stump carcinoma, at least in Western Europe, is estimated to be increased twofold compared with the normal population. But in Korea there has been one report. Recently we experienced a case of carcinoma of the stump which developed about 20 years after a gastro-jejunostomy for a duodenal ulcer.